Study of Palm Oil Shell Utilization as Metallurgical Coke with Variation of Bondcrete Additive - Hariyadi, Asful; Khoirunnisa Hidayat, Dinda; Purwanto, Moch. (Politeknik Negeri Malang, 2024)
Coke, an essential ingredient in the steel and metallurgical industries, is typically derived from bituminous coal. However, in Indonesia, where bituminous coal is rare, coke production is dependent on coal imports due to the high moisture content of local coal. An alternative approach is to use biomass, such as palm oil processing waste, for